2017
DOI: 10.1093/aje/kwx041
|View full text |Cite
|
Sign up to set email alerts
|

Modeled and Perceived Exposure to Radiofrequency Electromagnetic Fields From Mobile-Phone Base Stations and the Development of Symptoms Over Time in a General Population Cohort

Abstract: We assessed associations between modeled and perceived exposure to radiofrequency electromagnetic fields (RF-EMF) from mobile-phone base stations and the development of nonspecific symptoms and sleep disturbances over time. A population-based Dutch cohort study, the Occupational and Environmental Health Cohort Study (AMIGO) (n = 14,829; ages 31-65 years), was established in 2011/2012 (T0), with follow-up of a subgroup (n = 3,992 invited) in 2013 (T1; n = 2,228) and 2014 (T2; n = 1,740). We modeled far-field RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 51 publications
3
14
0
1
Order By: Relevance
“…Today, the prevailing interpretation is that the persons affected are in poorer health because they consider themselves more exposed, and as a result tend to develop nocebo responses [Baliatsas et al, ]. However, it is also plausible that these persons consider themselves more exposed because they are in poorer health, which leads them to seek causes in their environment [Martens et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Today, the prevailing interpretation is that the persons affected are in poorer health because they consider themselves more exposed, and as a result tend to develop nocebo responses [Baliatsas et al, ]. However, it is also plausible that these persons consider themselves more exposed because they are in poorer health, which leads them to seek causes in their environment [Martens et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Autorzy stwierdzili w nim występowanie związku między ogólną liczbą zgłaszanych dolegliwości subiektywnych, a postrzeganiem ekspozycji; wskazali natomiast brak istotnego statystycznie związku między występowaniem dolegliwości, a ekspozycją oszacowaną z zastosowaniem modelu geoprzestrzennego. Wykazano jednak niewielki, nieistotny statystycznie wzrost częstości zawrotów głowy i uczucia ucisku w klatce piersiowej wraz ze wzrostem oszacowanej ekspozycji [15].…”
Section: Działanie Biologiczne Pem Planowanych Do Wykorzystania W Sysunclassified
“…Few studies have addressed the occurrence of symptoms such as headache, tinnitus and other somatic complaints in relation to prospectively collected information on RF-EMF exposure 11 , 12 . A Swiss study reported no association between mobile phone use and tinnitus or overall symptom score, but it had limited statistical power to assess the occurrence of outcomes among people free from the conditions at baseline, due to a relatively small sample size ( n = 1122) and only 1 year of follow-up 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A Swiss study reported no association between mobile phone use and tinnitus or overall symptom score, but it had limited statistical power to assess the occurrence of outcomes among people free from the conditions at baseline, due to a relatively small sample size ( n = 1122) and only 1 year of follow-up 11 . A Dutch study found no association with sleep disturbances or other symptoms and focused on exposure from base stations rather than mobile phone use 12 . In a large Danish cohort study of mobile phone subscribers, increased rates of hospitalizations for migraine and vertigo among subscribers were reported, but the study had no information on amount of mobile phone use and confounders were limited to age, sex and calendar period, due to the register-based approach 13 .…”
Section: Introductionmentioning
confidence: 99%